HPLC-HRESI-MSn Characterization of Polyphenolic Compounds in the Stem Bark of Chlorophora regia A. Chev (Moraceae) - James Oppong-Kyekyeku; Samuel Oppong Bekoe; Edmund Ekuadzi; John Nii Adotey Addotey; Samuel Asare-Nkansah (Faculty of Pharmacy, Universitas Mulawarman, Samarinda, Indonesia, 75117, Gedung Administrasi Fakultas Farmasi Jl. Penajam, Kampus UNMUL Gunung Kelua, Samarinda, Indonesia, 2022)
Isolation and identification of secondary metabolites from medicinal plants could be tedious and time consuming. Therefore, any technique that could be used to confirm the identity of medicinal plant constituents without isolating them will save time and resources. Chlorophora similar to many genera in the Moraceae family have been demonstrated to be rich sources of polyphenolic compounds with important biological activities. The current study was designed to employ HRESI-MSn analyses to qualitatively examine isolated polyphenolic compounds from the stem bark of Chlorophora regia. Based on the HRESI-MSn data obtained, the fragmentation patterns of the compounds under study will be proposed and could be used in their identification in a matrix. Five polyphenolic compounds were successfully isolated and purified using various chromatographic techniques including column chromatography, thin-layer chromatography (TLC) and preparative HPLC. The structures of the isolated compounds were elucidated by in-depth analyses of their 1D and 2D NMR and mass spectroscopic data. HRESI-MS/MS was further used to characterize the isolated compounds. Five polyphenolic compounds including three Diels-Alder type adducts: sanggenon C, kuwanol E and chalcomoracin; two stilbene derivatives: chlorophorin and isochlorophorin were isolated from the stem bark. The tandem MS fragmentation patterns of the compounds in positive mode, were successfully proposed. The fragments obtained and proposed fragmentation patterns of the isolated compounds could be employed qualitatively in the identification of the studied polyphenolic compounds in a matrix.